Electroacupuncture Upregulates SIRT1-Dependent PGC-1α Expression in SAMP8 Mice - Dong, Weiguo (Med Sci Monit, 2015)
BACKGROUND: Abnormalities of brain energy metabolism are involved in Alzheimer disease (AD). Sirtuin 1 (SIRT1) is a class III histone deacetylase and activates peroxisome proliferator-activated receptor-γ co-activator-1α (PGC-1α), which enhances mitochondrial biogenesis and energy homeostasis. Electroacupuncture (EA) has been reported to improve brain energy metabolism in AD. However, the effect of EA on SIRT1 and PGC-1α in AD remains unclear. MATERIAL/METHODS: ATP levels were measured using assay kits in the hippocampus and frontal cortex of senescence-accelerated mouse prone 8 (SAMP8) mice. Western blotting analysis and quantitative real-time RT-PCR were performed to measure the expression of SIRT1 and PGC-1α in the hippocampus of SAMP8 mice. PGC-1α acetylation was analyzed using immunoprecipitation. RESULTS: Compared with senescence-accelerated resistant mice 1 (SAMR1) mice, SAMP8 mice had a decline in ATP levels and the expression of SIRT1 and PGC-1α. EA treatment improved ATP levels, upregulated the expression of SIRT1 and PGC-1α, and decreased PGC-1α acetylation. CONCLUSIONS: These data suggest that EA improved brain energy metabolism, potentially associated with the upregulation of SIRT1-dependent PGC-1α expression.